Disseminated Intravascular Coagulation in Emergency Department Patients With Primary Postpartum Hemorrhage. Issue 3 (September 2017) - Sohn, Chang Hwan; Kim, So Ra; Kim, Youn-Jung; Seo, Dong Woo; Ahn, Shin; Lee, Yoon-Seon; Lee, Jae Ho; Oh, Bum Jin; Won, Hye-Sung; Shim, Jae-Yoon; Lim, Kyoung-Soo; Kim, Won Young
Abstract : ABSTRACT: The aim of this study was to evaluate the prevalence of disseminated intravascular coagulation and to determine whether the presence of disseminated intravascular coagulation is associated with major adverse events in patients with primary post-partum hemorrhage (PPH) who present to the emergency department. This retrospective case-control study was conducted in the emergency department of a university-affiliated, tertiary referral center between January 1, 2004 and December 31, 2013. Patients were classified into disseminated intravascular coagulation (disseminated intravascular coagulation score ≥ 5) and non-disseminated intravascular coagulation groups. The two groups were compared in terms of clinical characteristics and the occurrence of major adverse events, defined as massive transfusion (≥ 10 units of packed red blood cells within 24 h of emergency department admission), invasive intervention (uterine artery embolization or emergency hysterectomy), hospital days, ventilator-free days, intensive care unit admission, intensive care unit-free days, and in-hospital mortality. Among 255 patients with primary PPH, 57 patients (22.4%) had overt disseminated intravascular coagulation. The disseminated intravascular coagulation group had significantly lower hemoglobin, hematocrit, platelet counts, and fibrinogen levels than the non-disseminated intravascular coagulation group; in addition, they had higher prothrombin times, and D-dimer levels ( P < 0.01). The occurrence of major adverse events was greater in the disseminated intravascular coagulation group than in the non-disseminated intravascular coagulation group (96.5% vs. 44.4%, P < 0.01). In conclusion, disseminated intravascular coagulation was frequently found in combination with primary PPH, and the outcome was worse in these patients than in those without disseminated intravascular coagulation.